2018
DOI: 10.1186/s13550-018-0415-3
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluciclovine PET discrimination between high- and low-grade gliomas

Abstract: BackgroundThe ability to accurately and non-invasively distinguish high-grade glioma from low-grade glioma remains a challenge despite advances in molecular and magnetic resonance imaging. We investigated the ability of fluciclovine (18F) PET as a means to identify and distinguish these lesions in patients with known gliomas and to correlate uptake with Ki-67.ResultsSixteen patients with a total of 18 newly diagnosed low-grade gliomas (n = 6) and high grade gliomas (n = 12) underwent fluciclovine PET imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…F-Fluciclovine images showed high contrast, confirmed by the high tumor-to-brain ratios (tumor SUVmax-to-SUVmean of a reference normal-brain region), concordant with the first clinical studies [10][11][12][13][14]. Our results showed that the two ratios calculated with two different reference regions (either the contralateral normal brain tissue or the cerebellum) are highly correlated, as was previously described by Kondo et al [10].…”
supporting
confidence: 90%
See 3 more Smart Citations
“…F-Fluciclovine images showed high contrast, confirmed by the high tumor-to-brain ratios (tumor SUVmax-to-SUVmean of a reference normal-brain region), concordant with the first clinical studies [10][11][12][13][14]. Our results showed that the two ratios calculated with two different reference regions (either the contralateral normal brain tissue or the cerebellum) are highly correlated, as was previously described by Kondo et al [10].…”
supporting
confidence: 90%
“…All 18 F-Fluciclovine and 11 C-Methionine visual and SUV analyses were conducted using the Hermes HybridViewer imaging software (Hermes Medical Solutions, Stockholm, Sweden) based on a summed 25-45 min PET static image set registered to a contrast-enhanced MR (or in one case CT) image acquired within 30 days of the PET image. We chose to base our analysis upon a summed 25-45 min image because the uptake was relatively stable over this time period; it was the latest time consistently acquired across patients for both 18 F-Fluciclovine and 11 C-Methionine and it was similar to time points used in other studies of 18 F-Fluciclovine uptake into brain tumors [10,12].…”
Section: Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In its first application of a single test patient with residual glioblastoma, fluciclovine demonstrated rapid uptake in tumor compared to normal brain tissue, suggesting its potential value as an imaging agent . Subsequent clinical trials then confirmed its utility in distinguishing high‐grade from low‐grade gliomas compared to established radiopharmaceuticals . Its efficacy was attributed to an affinity for tumor tissue as well as a hypothesized resistance to metabolism during cellular uptake…”
Section: Introductionmentioning
confidence: 95%